The Effect of Tax Heterogeneity on Prices and Volume around the Ex-Dividend Day: Evidence from the Milan Stock Exchange - Michaely, Roni; Murgia, Maurizio (Review of Financial Studies, 1995)
To investigate the effect of taxation on stock price and trading volume around the ex-dividend day, we use the Italian stock market, where dividends on two classes of stock are taxed differently. We find that the weighted average of investors' tax rates is reflected in the ex-day prices and the variance of the relative tax rate across investors is reflected in the volume of trades. We also show that higher transaction costs result in higher ex-dividend day excess returns and lower abnormal volume. This finding is consistent with ''profit elimination'' activity by institutions and corporations.